(No) Hope for the future? A design agenda for rewidening and rewilding higher education with utopian imagination - Rikke Toft Nørgård; Kim Holflod (International Journal of Educational Technology in Higher Education, 2024)
Abstract This article argues for exploring, connecting, and applying utopian imagination, speculative design, and planetary thinking as a way forward for higher education to reimagine and move towards more hopeful planetary futures. It examines hopepunk and solarpunk perspectives on possible futures to propose a design agenda for rewidening and rewilding higher education and educational technology with utopian imagination. Firstly, the article outlines and develops a framework for wider and wilder futures in higher education, emerging from utopian thinking and desire. Secondly, it connects hopepunk with speculative design and solarpunk with planetary design to highlight and put forward rebellious strategies of hope in envisioning more preferable futures. Thirdly, it approaches the field of educational technology within the context of wide and wild education to establish four planetary orientations concerning educational technology: Higher Education for, in, with, and by the world. Taken together, the article proposes a design agenda for educational technology that integrates utopian imagination and solarpunk practices with planetary educational technology to catalyse the development of more preferable futures in a more-than-human world.